The Existence of Overall Satisfaction in Service Customer Relationships - Zulganef, Zulganef (Gadjah Mada International Journal of Business, 2006)
Garbarino and Johnson (1999) find that there is no correlation between overall satisfaction and loyalty in the field of customer relationship. Their finding indicates that satisfaction is no longer an important issue in managing service organizations. This research investigates the existence of satisfaction in service organizations, which have relationships with customers. Contrary to Garbarino and Johnsonâs (1999) finding, this research finds that overall satisfaction, through commitment, has a relationship with loyalty. Hence, customer satisfaction is still a main issue with respect to managing service organizations, especially service organizations that have customer-relationship strategy. Survey method was conducted to test 12 hypotheses, and the sample of this research is customers of credit cardholders and supermarket cardholders. Sample size is 382 consisting of 196 (51.3%) credit cardholders and 186 (48.7%) supermarket cardholders. Data were analyzed using two-step structural equation modelling technique. In addition, this research also shows that investigators and managers should pay attention to affects, because affects have a unique role in relationship customer behavior.